Cataloguing in the open - the disintegration and distribution of the record - Martin Malmsten (JLIS.it, 2013)
As part of a strategic investment in openness the Swedish National Library has released the National Bibliography and accompanying authority file as open data with a Creative Commons Zero license effectively putting it in the public domain. The data has been available  as linked open data since 2008 but is now also released in its original, complete form making it fit for re-use by other library systems. An important principle of linked data is to link out the other datasets. However, as data becomes more interconnected and distributed the need for ways to track and respond to changes in other datasets, even ones outside our area of control, becomes bigger. The issue of who to trust of course becomes vitally important. This paper details the motivation behind the release as well as the technology used to support it. Also, a consequence of exposing and using linked data is that the idea of the record as a self contained and delimited entity starts to fall apart.